Pengaruh pajak daerah dan retribusi daerah serta dana bagi hasil terhadap belanja modal di kabupaten malinau - Mardi Franlius; Sri Mintarti; Yana ulfah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study was to determine the effect of Local Taxes and Levies and Funds For Capital simultaneously on Capital Expenditure, and the influence of Regional Tax on Capital Expenditure, influence Levies on Capital Expenditure and influence of Funds For Capital on Capital Expenditure. This study was conducted in Malinau North Borneo. Retrieval of data as supporting data is done in the office of the Department of Revenue Malinau District and the Central Bureau of Statistics Malinau District. As for the bleary-eyed analysis used multiple linear regression analysis. The results showed that the Local Taxes and Levies and DBH together (simultaneously) effect on Capital Expenditure in Malinau. Local Taxes positive and significant impact on Capital Expenditure in Malinau. Levies positive and not significant to the Capital Expenditure in Malinau and Funds For Capital proved to be positively and significantly to the Capital Expenditure in Malinau. Dominant influence on the local tax Capital Expenditure in Malinau.